2019
DOI: 10.1002/joe.21910
|View full text |Cite
|
Sign up to set email alerts
|

Doing business in China: Challenges and opportunities

Abstract: Though increasingly attractive to Western investors, China can be a daunting environment in which to start a business because of the opacity of the cultural norms and a growing sense of nationalism. An analysis of 20 years of research and local experiences highlights the modern entrepreneurial spirit that currently co‐exists with complex, traditional values in China. By better understanding the nuances of these traditions and the context in which they are most commonly manifested, Western businesspeople can fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Furthermore, some studies demonstrated that consumers' sustainable behaviours are influenced by social, situational and other factors, which tend to vary across national and consumer contexts (Nguyen & Johnson, 2020). In the context of Chinese cultural, complex systems exist for constructing interpersonal relationships for social functioning, such as guanxi and mianzi (Anglès, 2019). Therefore, some social factors, such as social norms, collective efficacy, interpersonal network relationships and traditional values, are also emphasised in the EV adoption literature (Berneiser et al, 2021; Chen et al, 2019; Jansson et al, 2011; Jansson et al, 2017; Li et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, some studies demonstrated that consumers' sustainable behaviours are influenced by social, situational and other factors, which tend to vary across national and consumer contexts (Nguyen & Johnson, 2020). In the context of Chinese cultural, complex systems exist for constructing interpersonal relationships for social functioning, such as guanxi and mianzi (Anglès, 2019). Therefore, some social factors, such as social norms, collective efficacy, interpersonal network relationships and traditional values, are also emphasised in the EV adoption literature (Berneiser et al, 2021; Chen et al, 2019; Jansson et al, 2011; Jansson et al, 2017; Li et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…2.1 The Chinese market and international business Over the past decades, emerging markets such as China have attracted Western business investment (Anglès, 2019;Fuzhong et al, 2019;Lemoine, 2013). China is one of the countries with the highest foreign direct investment (FDI), which is closely related to its established manufacturing capacity (Miniesy and Tarek, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Chinese firms develop guanxi as a strategic mechanism to overcome disadvantages by cooperating and exchanging favors with competitors and government authorities. Essentially, guanxi is a system of mutual obligations, assurances, and understandings (Anglès, 2019).…”
Section: Failing To Understand Cultural Differencesmentioning
confidence: 99%
“…Finding appropriate personnel emerged as a key factor for SiChuan Road & Bridge, but not for the other three cases. The organizational structure of the company follows that of traditional Chinese management practice (Anglès, 2019), and those closest to the leaders of the company were the most likely to be promoted (personal interview, March 2020). In contrast, the three other Chinese companies staffed their Norwegian subsidiaries with appropriately skilled and qualified people, who understood the local situation, and gave them appropriate levels of responsibility.…”
Section: Failing To Choose the Right Personnelmentioning
confidence: 99%